2012
DOI: 10.3174/ajnr.a3310
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Lenticulostriate Arteries by Flow-Sensitive Black-Blood MR Angiography on a 1.5T MRI System: A Comparative Study between Subjects with and without Stroke

Abstract: BACKGROUND AND PURPOSE:The branches of the LSA are the main causative arteries for lacunar infarction, though the vascular changes are largely unknown. Herein, we examined the correlation of LSA imaging findings in patients with lacunar infarction compared with controls by using FSBB-MRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…3 Investigations using flow-sensitive black-blood MRA with MR imaging have confirmed that it is superior for visualizing LSA branches in patients with stroke. 11,15 Other studies using 7T MR imaging have reported advanced noninvasive methods for visualization of the cerebral microvasculature, including the LSAs. 16,17 However, it is not easy to image the LSA when using TOF-MRA with conventional 1.5T MR imaging systems, which is the most prevalent technique currently available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Investigations using flow-sensitive black-blood MRA with MR imaging have confirmed that it is superior for visualizing LSA branches in patients with stroke. 11,15 Other studies using 7T MR imaging have reported advanced noninvasive methods for visualization of the cerebral microvasculature, including the LSAs. 16,17 However, it is not easy to image the LSA when using TOF-MRA with conventional 1.5T MR imaging systems, which is the most prevalent technique currently available.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating the LSAs on MR imaging and CTA determined the number of LSA branches within 5 mm from the MCA and the number of branches beyond 5 mm. 11,12 The number of LSAs, defined as those longer than 5 mm, were analyzed. 12 Two boardcertified radiologists (K.M.…”
Section: Image Postprocessing and Data Analysismentioning
confidence: 99%
“…High-resolution computed tomography angiography and flow-sensitive black-blood magnetic resonance angiography (MRA) may be useful to detect small perforating arteries. 15 , 16) Ultrahigh-field MRA with 7.0T may be promising with respect to visualizing these small vessels. 17) …”
Section: Discussionmentioning
confidence: 99%
“…Flow-sensitive black-blood magnetic resonance angiography (FSBB-MRA) is a recently introduced noninvasive black-blood imaging technique for visualizing perforating arteries. 7 , 8) High-resolution 3-tesla FSBB-MRA can reveal tiny parenchymal arteries as well as cisternal and ventricular arteries in the coronal view of the brain. As of this writing, no previous report has addressed the use of FSBB-MRA in visualization of abnormal collateral vessels in moyamoya disease.…”
Section: Introductionmentioning
confidence: 99%